Payrolling – outsourcing in human resource management - Herdan, Agnieszka; Stuss, Magdalena M. (Contemporary organisation and management. Challenges and trends, 2020)
The intensified globalization process, the fast-growing development of Information Technology, and the necessity to reduce operating costs, force companies to look for more efficient ways of using resources. Outsourcing some of the operation to external providers can be a good way to reduce cost. Payroll outsourcing can offer various benefits, such as lowering operational costs, access to the newest technologies and expertise without involving extensive use of resources. This is only possible if a reliable provider that is financially sound and trustworthy is available. This paper investigates the benefits that can be gained by outsourcing the payrolling function. Outsourcing will be defined and its benefits discussed, followed by an analysis of payrolling within Human Resource Management (HRM) outsourcing. Finally, the benefits of outsourcing of the payrolling function will be presented.